Introduction to engineering materials behavior, properties, and selection - Murray, G. T. 1927- (Materials engineering (Marcel Dekker, Inc.), 1993)
Presents the fundamental science needed to understand the classification of materials and the limits of their properties in terms of temperature, strength, ductility, corrosion and physical behaviour, while emphasizing materials processing, selection and property measurement methods.